2013
DOI: 10.4314/gjpas.v19i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented and unfermented Mucuna bean seed, on growth performance of tilapia

Abstract: The effect of fermented and unfermented Mucuna (Mucuna pruriens utilis) seed on growth performance of the Nile Tilapia, Oreochromis niloticus (L.) Trewavas, was investigated in eight weeks feeding trial in concrete tanks. Three approximately isonitrogenous diets were fed to three sets of fingerlings of Oreochromis niloticus. Specific growth rate (SGR), average weight gain, (AWG), percentage weight gain (FWG), food conversion ratio (FCR) and protein efficiency ratio (PER) were not significantly different (P>0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The feed conversion ratio of tilapia (O. niloticus) with the addition of M. pruriens fermentation showed an FCR value of 1.19 and feed efficiency of 84% [11]. Manwhile, the addition of velvet bean flour to Pangasius sp.…”
Section: Introductionmentioning
confidence: 99%
“…The feed conversion ratio of tilapia (O. niloticus) with the addition of M. pruriens fermentation showed an FCR value of 1.19 and feed efficiency of 84% [11]. Manwhile, the addition of velvet bean flour to Pangasius sp.…”
Section: Introductionmentioning
confidence: 99%
“…Tuan et al (2020) documented that M. pruriens beans can replace Vicia faba beans in common carp (Cyprinus carpio) production. Research carried out by Woke et al (2013) has shown that an unfermented Mucuna diet can conveniently replace Soya bean-based diet for feeding Oreochromis niloticus. Telfairia occidentalis has been used as a feed additive in African catfish, C. gariepinus, the result suggested that dietary supplementation with T. occidentalis leaf powder improved the growth, feed utilization, and survival of C. gariepinus fingerlings.…”
Section: Introductionmentioning
confidence: 99%